Preparation of high crystallinity cellulose nanocrystals (CNCs) by ionic liquid solvolysis - Tan, Xiao Yun; Hamid, Sharifah Bee Abd; Lai, Chin Wei (Elsevier, 2015)
High crystallinity cellulose nanocrystals (CNCs) were successfully prepared from microcrystalline cellulose (MCC) by utilization of 1-butyl-3-methylimidazolium hydrogen sulfate (BmimHSO4) as both catalyst and solvent. Interestingly, it was found that crystallinity of CNCs was improved with increase in temperature which attributed to selective removal of the amorphous phase of cellulose performed at a higher rate with higher temperature. The successful conversion of MCC to CNCs was supported by HRTEM in which the uniform rod-like shape of CNCs was obtained. CNCs with diameter range from 15 to 20 nm and length range from 70 to 80 nm were successfully produced at 90 °C with BmimHSO4. In the present work, CNCs synthesized at different temperatures from 70 °C to 100 °C were investigated. The application of BmimHSO4 as both catalyst and solvent introduced a green chemistry approach as it does not produce any hazardous waste products and is an economical process because the recovery of ionic liquid is high (>90%).